2019
DOI: 10.5851/kosfa.2018.e38
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein from Egg Yolk (EYHDL) Improves Dyslipidemia by Mediating Fatty Acids Metabolism in High Fat Diet-induced Obese Mice

Abstract: We investigated the effect of high density lipoprotein from egg yolk (EYHDL) on serum, hepatic and fecal lipid and fatty acids (FAs) levels and on gene expression involved in FAs metabolism. Male KM mice were fed either normal diet (ND; n=20), high fat diet (HFD; n=20), or high fat diet containing EYHDL (EYHDL; 0.6 mg/g, every day by oral gavage, n=20) for 100 days. At the end of the experiment, the effects of treatments on biochemical parameters, FAs profiles and involved gene expression were analyzed. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…The biochemical results demonstrated that EY did not induce lipid accumulation in serum and liver in ND diet, and EY could effectively modify the lipid profiles in serum and liver by increasing HDL‐C, decreasing LDL‐C in serum, and thus attenuated hyperlipidemia in HFD. This is consistent with previous reports in our lab showing that EY‐enriched diet could lower serum TG, TC, LDL‐C, hepatic TG, and cholesterol concentrations than those fed normal diet in rats or mice …”
Section: Discussionsupporting
confidence: 93%
“…The biochemical results demonstrated that EY did not induce lipid accumulation in serum and liver in ND diet, and EY could effectively modify the lipid profiles in serum and liver by increasing HDL‐C, decreasing LDL‐C in serum, and thus attenuated hyperlipidemia in HFD. This is consistent with previous reports in our lab showing that EY‐enriched diet could lower serum TG, TC, LDL‐C, hepatic TG, and cholesterol concentrations than those fed normal diet in rats or mice …”
Section: Discussionsupporting
confidence: 93%
“…In the present study, feeding of HFD to male rats increased plasma TC, TG and LDL-c, while it results in a decrease of HDL-c, compared to control rats. There is consistency between our findings and that reported by Yu et al [26] and Barakat and Mahmoud [27] . The observed dyslipidemia was explained by the disorders of lipid metabolism by HFD [26] .…”
Section: Discussionsupporting
confidence: 93%
“…There is consistency between our findings and that reported by Yu et al [26] and Barakat and Mahmoud [27] . The observed dyslipidemia was explained by the disorders of lipid metabolism by HFD [26] . High levels of FAs can result in increased intracellular TG synthesis and formation of lipid droplets in serum and liver [28] .…”
Section: Discussionsupporting
confidence: 93%
“…Histological analysis. The liver tissue was fixed in paraffin and cut into 3-m thick sections (27). The sections were stained with hematoxylin and eosin (H&E), and the stained sections were observed under a microscope.…”
Section: Methodsmentioning
confidence: 99%